2010
DOI: 10.4081/ijas.2010.e67
|View full text |Cite
|
Sign up to set email alerts
|

Effects on egg yolk colour of paprika or paprika combined with marigold flower extracts

Abstract: COLOR-UP® and COLOR-UP YELLOW-S

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
20
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 11 publications
7
20
2
Order By: Relevance
“…It indicated that the use of marigold up to 3 g could not affect the palatability of layer pullets and therefore feed intake was found to be non-significant. Results on feed consumption agreed well with the results of Ferdaus et al (2008), Lokaewmanee et al (2010), Mansoori et al (2008), Cho et al (2013) and Amar et al (2013) who reported that dietary inclusion of pigment rich herbs did not reduce the consumption of mixed feed.…”
Section: Advances In Animal Andsupporting
confidence: 82%
See 3 more Smart Citations
“…It indicated that the use of marigold up to 3 g could not affect the palatability of layer pullets and therefore feed intake was found to be non-significant. Results on feed consumption agreed well with the results of Ferdaus et al (2008), Lokaewmanee et al (2010), Mansoori et al (2008), Cho et al (2013) and Amar et al (2013) who reported that dietary inclusion of pigment rich herbs did not reduce the consumption of mixed feed.…”
Section: Advances In Animal Andsupporting
confidence: 82%
“…Carotenoids from egg yolk are more bio-available compared to spinach or pigment supplements. In a study, where hens fed with diets containing yellow xanthophylls extracted from Tagetes recorded the improvement in Roch yolk Colour Score up to 11.7 (Ferdaus et al, 2008;Karadas et al, 2006;Lokaewmanee et al, 2010). Similarly, Marigold feed additives fed to quails enhanced the enrichment of total carotenoids in quail eggs (Karadas et al, 2006).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Further, inbreds with enhanced lutein and zeaxanthin can be potentially exploited for developing hybrids for poultry industry. Consumers generally prefer yellow-orange egg yolk as compared to off-white yolk (Lokaewmanee et al 2010;Liu et al 2012) and poultry industry often utilize extracts from petals of marigold flower containing high xanthophylls like lutein and zeaxanthin as egg colorant in feed, as chicken has a natural ability to deposit these molecules into their egg yolks (Galobart et al 2004;Lokaewmanee et al 2010). Thus, inbreds with high lutein and zeaxanthin identified in the study can be used in developing hybrids specifically for poultry industry, the major consumer of maize production in Asia.…”
Section: Discussionmentioning
confidence: 99%